EXPLORING TEACHING AND LEARNING APPROACHES FOR CHILDCARE AT NAS SAYANG CHILDCARE - SYARFA AKILA MATTA@MASE; MOHD NAZRI ABDUL RAHMAN (P3I UMSurabaya, 2025)
This study examines the implementation of teaching and learning approaches for infants and toddlers in Malaysian childcare centers, emphasizing child-centered practices that foster holistic development. Using library research and an online interview with an experienced childcare teacher, the findings indicate that childcare educators apply a child-centered approach consistent with Jean Piaget’s Theory of Cognitive Development. Activities are designed according to children’s developmental stages to promote cognitive, social, emotional, and physical growth. The study also highlights parents’ active involvement and expectations regarding transparent communication, safety, and nurturing care. Findings show that effective early childhood education depends on collaboration between educators and parents. Furthermore, the study recommends expanding play-based learning and integrating Internet of Things (IoT) technology to enhance transparency, efficiency, and engagement in childcare management. Overall, the results stress that combining developmental theories, parental engagement, and innovative strategies ensures early education remains relevant to 21st-century family needs.